Cochlear implantation in a child with cystic cochleovestibular malformation: a case report - Komang Andi Dwi Saputra; Adriyani Hartayanti (DiscoverSys Inc., 2020)
Background: The inner ear and internal auditory canal (IAC) malformations account for 20% of congenital sensorineural hearing loss in children. The cystic cochleovestibular malformation is one of the congenital malformations in the cochlea, in which the cochlea is empty, unpartitioned, and cystic. The dimension of the cochlea is normal. This presents a significant challenge even to the most experienced clinicians because of difficulty in the surgery with facial nerve anomaly and gusher, choice and placement of electrode, and increased risk of meningitis after the procedure. This study aims to report the procedure of cochlear implantation in one case of cystic cochleovestibular (IP type I) malformation, which still became a challenge in the otology field.Case Presentation: We reported one case of 5 years old boy with bilateral cystic vestibular malformation who underwent cochlear implantation on the left ear. The patient was diagnosed with bilateral profound congenital sensorineural hearing loss. He already used hearing aids on both ears but gained limited improvements. Peri-operative perilymph gusher was happened and was stopped by plugging the cochleostomy hole using fascia. The patient showed good condition after the procedure. Although facial nerve lesion occurred after the operation, it was improved by giving steroids. There is no sign of cerebrospinal fluid leaks such as rhinorrhea, otorrhea, or meningitis.Conclusion: This report showed good outcomes following cochlear implantation in cystic cochleovestibular malformation.